A megyei jogú városok, mint innovációs potenciál hordozók (Cities With County Rights as Carriers of Innovational Potential) - Judit Berkes (DETUROPE)
The examination of cities’ innovational potential has been in the focus of attention for regional studies, however, there are only a few researches that carried out a complex examination that would embrace the entire Hungarian city-network. The exploratory examination of cities’ success is determinative, since in the competitive situations characteristic of today’s world, strategies well-developed for results could serve to better their position, although it is not only science seeking for answers but politics as well, for the strengthening of their position is an important task. The basis for our study is an examination carried out in 2005, whose methodology we kept, only the variables that were considered irrelevant in this study were modified. The Hungarian city-network has formed and changed during this time; there are some settlements that could actually keep their central role, however, there are also examples that certain cities could not reach such a level of development that they would be added to the 23 outstanding ones. The examination made it possible to explore the differences within the Hungarian city-networks, as well as to shed light to the degree of innovational capabilities of the well-confinable groups of city-networks. The results show that the difference between the separate groups is increasing, but the differences between cities that belong together is decreasing. It is important to highlight that in the case of the cities performing excellent compared to the Hungarian settlements’ average achievement, the innovational and economic potential mostly do not meet, except in the case of a few cities with outstanding results.